Comparing functional traits of planted Eucalyptus sp. genotypes managed as high tree and coppice - Costa, Jenickson Rayron da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
In this dissertation, we aimed to evaluate the potential of rapidly measured leaf water relations traits for the phenotyping of drought tolerance across the 21 commercial Eucalyptus genotypes, and subsequently, to compare the drought tolerance of Eucalyptus genotypes managed as high forest and coppice stand. The reason for this hypothesis is that, due to a root system developed from the initial development phase, Eucalyptus genotypes managed as coppice experience less water stress in the first years of the rotation. Therefore, Eucalyptus genotypes managed as coppice are less resistant to drought, due to plasticity in drought tolerance traits. The field experiment was installed in February 2018 in Itatinga, São Paulo state, Brazil. We found that πo and Ψtlp exhibit a significant seasonal plasticity. Only the measurements conducted at the end of the dry season were associated to some extent with the expected drought tolerance of the Eucalyptus genetic materials. Although we confirmed that variation in Ψtlp is mostly driven by variation in πo across Eucalyptus material, the osmometer method was not able to accurately rank drought tolerance among the genotypes of our common-garden experiment. We found that the drought tolerance traits of coppice and high forest are similar. Contrary to expectations, plant drought tolerance predictor traits such as Ψtlp and Ψ50 are not influenced by management in commercial Eucalyptus genotypes. Conversely, the stand biomass, and leaf area index are more determinant for differences between silvicultural systems than drought tolerance traits. However, this warrants further investigation of management effects in conditions of higher water stress, in order to draw a more extensive picture of Eucalyptus vulnerability to drought.

Nesta dissertação, objetivou-se avaliar o potencial de rapidamente medir as características hídricas foliares para a fenotipagem da tolerância à seca de genótipos de Eucalyptus, e posteriormente, comparar a resistência à seca de genótipos de Eucalyptus manejados como alto fuste e talhadia. A justificativa para essa hipótese é que, devido a um sistema radicular desenvolvido desde a fase inicial de desenvolvimento, genótipos de eucalipto manejados como talhadia sofrem menos estresse hídrico nos primeiros anos da rotação. Portanto, genótipos de eucalipto manejados como talhadia são menos resistentes à seca, devido à sua plasticidade nas características de tolerância à seca. O experimento de campo foi instalado em fevereiro de 2018 em Itatinga, estado de São Paulo, Brasil. O experimento faz parte do Programa Cooperativo de Produtividade e Fluxos de Carbono e Água em Eucalipto (EUCFLUX). Observou-se que πo e Ψtlp exibem uma plasticidade sazonal significativa. Apenas as medições realizadas no final da estação seca foram associadas de alguma forma com a tolerância à seca esperada dos materiais genéticos de eucalipto. Embora tenha-se confirmado que a variação em Ψtlp é principalmente impulsionada pela variação em πo em material de eucalipto, o método do osmômetro não foi capaz de classificar com precisão a tolerância à seca entre os genótipos estudados. Foi observado que as características de tolerância à seca da talhadia e alto fuste são semelhantes. Ao contrário do esperado, características preditoras de tolerância à seca como Ψtlp e Ψ50 não são influenciados pelo manejo em genótipos comerciais de eucalipto. Por outro lado, a biomassa do estande e o índice de área foliar são mais determinantes para as diferenças entre os sistemas silviculturais do que as características de tolerância à seca. No entanto, isso merece uma investigação mais aprofundada dos efeitos do manejo em condições de maior estresse hídrico, a fim de traçar um quadro mais amplo da vulnerabilidade do eucalipto à seca.
Comparando atributos funcionais de genótipos de Eucalyptus sp. manejados como alto fuste e talhadia
Keywords: Silvicultural system; Drought tolerance; Vulnerability to cavitation; Water potential; Pressure-Volume curves; Ponto de perda de turgor; Vulnerabilidade à cavitação; Genótipos de Eucalyptus; Tolerância à seca